Relationship of Treponema pallidum to Acidic Mucopolysaccharides - Fitzgerald, T. J. (1979)
Attempts were made to relate Treponema pallidum to the acidic mucopolysaccharides that occur in vivo within host ground substance and in vitro on the surface of cultured testicular cells. Infected testicular tissue was fixed and processed for transmission electron microscopy in the presence of ruthenium red. The use of this inorganic dye demonstrated the large quantity of mucopolysaccharide within testicular tissue and the intimate association of treponemes with this material. Wheat germ agglutinin and soybean agglutinin agglutinated freshly harvested trypsinized testicular cells and trypsinized cultured cells derived from normal rabbit testes (NRT). When stained with toluidine blue, both cell preparations were metachromatic. Prior treatment of cultured NRT cells with hyaluronidase slightly decreased their sensitivity to agglutination by wheat germ agglutinin and soybean agglutinin. Lectin agglutination, metachromasia, and hyaluronidase susceptibility indicated that freshly harvested testicular cells and NRT cells have surface-associated acidic mucopolysaccharides that are probably hyaluronic acid and chondroitin sulfate. A rabbit erythrocyte “sandwich” technique was devised to show that hyaluronidase removed wheat germ agglutinin receptors from the cultured NRT cells. Prior incubation of NRT cells with hyaluronidase, followed by the addition of T. pallidum, resulted in a reduction in numbers of treponemes attached to the NRT cells. The attachment of T. pallidum appears to be mediated through the acidic mucopolysaccharides on the surface of NRT cells. The findings are discussed in terms of the importance of host ground substance mucopolysaccharide to the syphilitic infective process.